Investigation of the difference in color enhancement effect on cyanidin-3-O-glucoside by phenolic acids and the interaction mechanism. (15th June 2023) - Cao, Yan; Zhao, Baofu; Li, Yougui; Gao, Haiyan; Xia, Qile; Fang, Zhongxiang
Abstract: Co-pigmentation effect of phenolic acids on cyanidin-3-O-glucoside (C3G) and the mechanisms were investigated. Sinapic acid (SIA), ferulic acid (FA), p -coumaric acid ( p -CA) and syringic acid (SYA) significantly enhanced C3G stability ( P  < 0.05), whereas vanillic acid (VA) and gallic acid (GA) showed no influence ( P  > 0.05). Among these phenolic acids, SIA and FA had higher binding coefficient with C3G (48.83 and 43.38), reduced degradation rate constant by 40.0 ∼ 50.0 %, prolonged half-life by 74.6 ∼ 94.7 % at 323 K, and significantly inhibited C3G hydration reaction (p K h  = 2.87 and 2.80, P  < 0.05). Molecular docking revealed that C3G and co-pigments were connected by hydrogen bond and π-π stacking interaction. Hydroxycinnamic acids of SIA, FA and p -CA bound with ring B and ring C of C3G, while hydroxybenzoic acids of SYA, VA and GA hardly interacted with ring C. Generally, the protection effect of hydroxycinnamic acids on C3G was better than that of hydroxybenzoic acids, exhibiting stronger hyperchromic effect.